TERMINOLOGY AND KINSHIP TERMS (Proceedings of International Educators Conference, 2023)
This article is devoted to the problems of their specific characteristics, dictionary meanings and scope of application, taking into account the development of the terminology department of linguistics and the importance of field terms and the need for scientific-theoretical research of kinship terms, which are considered as one of the units of this department. 'worked out. The article examines the linguistic features of the terms related to kinship in the English and Uzbek languages.